FUNGSI SOSIAL SERAGAM DAN ATURAN BERBUSANA DI LEMBAGA PENDIDIKAN ISLAM - Adytia Maulana Zidqi , Muhammad; Hulwa, Febriana Hisana; Fitria, Habibatul; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
The implementation of school uniforms and dress code regulations in Islamic educational institutions is often understood merely as the fulfillment of religious norms. However, these practices also have important social functions in shaping students’ behavior and social life. This study aims to analyze the social functions of school uniforms and dress codes in Islamic educational institutions from the perspective of the sociology of education. The research employs a qualitative library research method through the analysis of academic books, scholarly journal articles, and official documents of Islamic educational institutions. Data analysis is conducted using content analysis and thematic analysis. The findings indicate that school uniforms and dress codes function as mechanisms for the internalization of moral values, the formation of collective identity, social control, the cultivation of discipline, and the creation of social equality within the school environment. Furthermore, dress practices contribute to the transfer of institutional values into students’ social lives in the wider community. Thus, school uniforms and dress codes can be regarded as a form of social investment in character formation, indicating that Islamic education is oriented not only toward academic achievement but also toward the development of individuals with strong social and moral awareness.